STABLE CARBON ISOTOPE COMPOSITIONS OF GASEOUS HYDROCARBONS PRODUCED FROM HIGH PRESSURE AND HIGH TEMPERATURE PYROLYSIS OF LIGNITE - Du J.; Jin Z.; Xie H.; Bai L.; Liu W. (My University, 2003)
Pyrolysis of lignite at high pressure and high temperature (HPT) was conducted to investigate the potential stable carbon isotopic fractionation of the produced gaseous hydrocarbons. The experiments were done in a closed system at temperatures of 500-700 °C and pressures of 1-3 gigapascals (GPas). Gas chromatography-combustion-isotope ratio mass spectrometric analysis (GC-C-irMS) of the produced gaseous hydrocarbons leads to two important observations. First, the distribution of the δ13C values for methane, ethane, propane and butane shows a clear reversal, with δ13C1 > δ13C2 >δ13C3 > δ13C4. The relatively 13C-enriched methane and 13C-depleted butane is in contrast to the widely accepted isotope distribution pattern of biogenic gases and is similar to that reported for abiogenic gases. Second, carbon dioxide produced from the pyrolysis of lignite is relatively enriched in 13C, with δ13C values (-18.6 to -22.3%%) that are much higher than those of the gaseous hydrocarbons and lignite itself (-26.8%%). These findings suggest a possible scenario that gaseous hydrocarbons can be generated from organic matter under the HPT conditions of the lower lithosphere, particularly in subduction regions where sedimentary organic matter might be introduced into the mantle, and that the reversal in the stable carbon isotopes of gaseous hydrocarbons may not be an exclusive indicator of abiogenic gases. Therefore, isotope criteria commonly used to differentiate biogenic from abiogenic gases should be used with caution.